Nuclear Dynamics and Electronic Eﬀects of Hydrogen on Solid Surfaces. Issue 2 (26th August 2016) - Fukutani, K.; Wilde, M.; Ogura, S.
Abstract: Hydrogen is involved in a variety of chemical processes on surfaces. While hydrogen exhibits vibrational and rotational dynamics in its adsorption state, it in some cases undergoes diffusion into the substrate as well as on the surface, and participates in chemical reactions. Furthermore, hydrogen exchanges an electron with surfaces having a significant effect on the surface electronic structure. In this personal account, we review our recent studies on surface nuclear dynamics of hydrogen, hydrogen transport across surfaces, catalytic hydrogenation/isotope exchange reactions, and charge transfer between the surface and hydrogen by using a depth‐resolved technique of nuclear reaction analysis and a quantum‐state‐selective detection of resonance enhanced multiphoton ionization in combination with surface science techniques. As a future prospect, we refer to ultraslow μ spin rotation spectroscopy for a direct probe of the hydrogen charge state at surfaces. Abstract : Hydrogen adsorbed on surfaces is involved in a variety of chemical processes while it exhibits vibrational and rotational dynamics in its adsorption potential. Furthermore, hydrogen exchanges an electron with surfaces having a significant effect on the surface electronic structure. In this personal account, we review our recent studies on surface nuclear dynamics, transport across surfaces, catalytic hydrogenation reactions, and charge transfer between the surface and hydrogen by using nuclear reaction analysis and resonance enhanced multiphoton ionization in combination with surface science techniques.